Effects of different doses of electron beam irradiation on bacterial community of Portunus trituberculatus. (August 2021) - Pan, Huijuan; Yu, Qi; Qian, Chenru; Shao, Haitao; Han, Jiajun; Li, Yongyong; Lou, Yongjiang
Abstract: Electron beam irradiation (EBI) can effectively kill microorganisms that cause food decay and thus, prolong the shelf life of food. However, different doses of EBI on the impact of Portunus trituberculatus microbial community structure remain to be seen. This study adopted high-throughput sequencing technologies to compare the effect of different doses of EBI on the microbial community structure of the swimming crab and found that the crab microbial community structure was changed significantly upon treatment with different doses of EBI. We combined alpha and beta diversity analysis, relative abundance analysis of species, and linear discriminant analysis effect size analysis, and our results focused on Psychrilyobacter, Clostridium, Vagococcus, Psychrobacter, and Carnobacterium . In addition, the richness and diversity of microorganisms initially decreased and then increased with the increasing of radiation dose. The results showed that the minimum dose of EBI was 6 kGy. This study provides a theoretical basis for the preservation of crabs. Graphical abstract: Image 1 Highlights: The effects of EBI on the microflora of Portunus trituberculatus were studied by 16S rRNA. Bacteria richness and diversity decreased firstly and then increased with increasing EBI dose. EBI may inhibit the growth of Pseudomonas bacteria to prevent the occurrence of BPS. Psychrobacter dominated the P. trituberculatus after 6 kGy dose of EBI.